(untitled) (Journal of the College of Basic Education, 2026)
This study aimed to develop a proposed model for a counseling supervision and training manual for the Palestinian Ministry of Education, in light of the current supervisory reality and the professional needs of counseling staff in educational institutions. The study employed a developmental qualitative research design, utilizing semi-structured interviews as the primary tool for data collection. This methodology was selected for its suitability in analyzing field practices and constructing a procedural model based on professional expertise. The study was conducted on a purposive sample of (8) participants, including psychological and educational supervisors, school counselors in government schools, and key stakeholders involved in organizing counseling supervision within the Ministry of Education and the Ministry of Social Development. The results revealed that current counseling supervision is characterized by a predominance of administrative and regulatory functions at the expense of clinical and supportive roles. Furthermore, the findings indicated a lack of consistency in supervisory practices and the absence of a unified manual to standardize the process. The results also highlighted an urgent need for developing supportive supervision models, providing specialized training, and adopting flexible supervisory mechanisms that keep pace with digital transformation. Based on these findings, the study recommends the adoption of the proposed model and suggests conducting future mixed-methods research to further consolidate and validate the counselling supervision manual.